Universities and the redevelopment politics of the neoliberal city - Bose, Sayoni (Urban studies (Edinburgh, Scotland), 2015)
This paper concentrates on universities as important actants in the neoliberal city, specifically through their engagement of development activities. The paper visualises universities as an entrepreneurial subject: a neoliberal institution which adopts the responsibility to redevelop. Towards that end, the paper situates the redevelopment activities of universities and their politics in the context of the neoliberal city. It subsequently identifies the causal structures that underpin the growth logic of universities, which form the condition for their engagement in redevelopment as entrepreneurial subjects. The paper argues that the pressures coming out of the accumulation process act as an impetus for universities to expand, for instance, to accommodate the increasing student enrolments that generate revenues for them. Given their size, specialised infrastructure and the localised logic of bringing students to campus, expansion often means expansion in situ. This puts the spotlight on universities' politics of redevelopment and the challenges they face as it typically means destruction of existing living and workplaces. Being entrepreneurial, universities maximise their efficiency in the politics of redevelopment to produce minimal resistance. This they do through alliance-building by creating amenable subjectivities that facilitate redevelopment. This is constituted by drawing upon and exacerbating existing cleavages of class and race. The paper presents a case study of redevelopment activities of The Ohio State University, located in Columbus, Ohio. The case study will illustrate why this university became an entrepreneurial subject and how, that is, through what discursive-material mechanisms the politics of persuasion unfolded, producing subjectivities that created (non)acquiescence around redevelopment.